Heterotopic Cesarean Scar Pregnancy: Diagnosis, Treatment, and Prognosis - OuYang, Zhenbo; Yin, Qian; Xu, Yujing; Ma, Yunyan; Zhang, Qiushi; Yu, Yanhong (Journal of ultrasound in medicine, 2014)
Heterotopic cesarean scar pregnancy is a rare, life‐threatening form of ectopic pregnancy. To provide information regarding the clinical manifestations, diagnosis, management, and prognosis of this condition, we reviewed all cases reported in the English literature. All literature on heterotopic cesarean scar pregnancy was retrieved by searching the PubMed database and tracking references of the relevant literature. Full texts were reviewed, and clinical manifestations, diagnostic methods, and the relationship between the treatment and prognosis were summarized. A total of 14 patients with heterotopic cesarean scar pregnancies were identified, including 6 spontaneous pregnancies and 8 following in vitro fertilization–embryo transfer. Gestational ages at diagnosis ranged from 5 weeks to 8 weeks 4 days. Only 5 cases presented with vaginal bleeding, and the others were asymptomatic. All 14 cases were diagnosed by transvaginal sonography. One patient with no future fertility requirements underwent pregnancy termination by methotrexate. Of the remaining 13 patients who desired to preserve their intrauterine gestations, 10 were treated by sonographically guided selective embryo reduction in situ (by embryo aspiration, drug injection, or both); 2 underwent laparoscopic and hysteroscopic excision of the ectopic pregnancy masses; and 1 was treated by expectant management. All operations were successful and maintained a living intrauterine gestation. Twelve cases resulted in live births by cesarean delivery (3 at term and 9 preterm). One patient underwent pregnancy termination at 12 weeks because of a fetal malformation confirmed by sonography. The possibility of heterotopic cesarean scar pregnancy after cesarean delivery should be considered, especially when pregnancy follows assisted reproductive technology. Transvaginal sonography is an important tool for diagnosis and management. Despite the many options, the best treatment for this condition remains unclear. Selective embryo reduction in situ with sonographic guidance is the main treatment modality and can result in a successful intrauterine gestation, albeit at high risk.